The needs for teaching media development physical education sports health (PJOK) with an interactive e-book for primary school students - Kusriani, Andri; Dewi, Muharika (Research in Education and Technology (REGY), 2024)
This research aimed to determine the feasibility and the needs for developing digital-based teaching media in elementary schools, as an alternative teaching media in implementing physical education, sports, and health (PJOK) learning for Phase B students at SDN 13 Sitiung. This development was relevant to students’ learning needs in which students can utilize digital technology in the PJOK learning process. The presence of this interactive e-book is hoped to increase motivation and student learning outcomes and provide changes in the PJOK learning process which should be adapted to the learning needs of students and the digital era.